Analisis Peran Financial Capability terhadap Financial Well-Being dengan mediasi pengguna QRIS - Keisya Novadila Putri; Liana Mangifera (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
The rapid growth of information technology in recent years has made it easier for people to carry out their daily activities. Financial technology is currently increasingly popular and developing rapidly, making it easier for the general public to access other financial products. Quick Response Code (QR Code) is a technological development used as a digital wallet payment technique. By using one standard QR code, product and service providers (merchants) do not have to have a different type of QR Code than the publisher. With the presence of several types of digital wallet applications, merchants need to provide as many QR code services as there are digital wallet applications available for delivery by each application. "This research will discuss the influence of using mobile banking as a mediation to link the impact of financial capabilities (financial behavior, financial attitudes, and financial knowledge) on financial well-being